2021
DOI: 10.1111/avj.13072
|View full text |Cite
|
Sign up to set email alerts
|

Cattle, climate and complexity: food security, quality and sustainability of the Australian cattle industries

Abstract: Background Marked increases in atmospheric CO2 concentrations are largely associated with the release of sequestered carbon in fossil fuels. While emissions of green‐house gasses (GHG) from cattle have significant global warming potential, these are biogenic sources and substantially involve carbon in natural cycles, rather than fossil fuel. Cattle use human inedible feeds and by‐products of human food production to produce nutrient‐dense foods of great value to humans. Interventions to reduce GHG production R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…This report also confirms the lifetime of CH 4 is 11.8 years in the atmosphere, making the potency much closer to 84 times as potent as carbon dioxide over the relevant approximately 20-year lifespan [63]. The argument for GWP* is supported in the literature, where the "*" represents the lifespan of the GHG in question [18,20].…”
Section: Methane Metric Challengessupporting
confidence: 68%
See 3 more Smart Citations
“…This report also confirms the lifetime of CH 4 is 11.8 years in the atmosphere, making the potency much closer to 84 times as potent as carbon dioxide over the relevant approximately 20-year lifespan [63]. The argument for GWP* is supported in the literature, where the "*" represents the lifespan of the GHG in question [18,20].…”
Section: Methane Metric Challengessupporting
confidence: 68%
“…Parra et al [51] assessed a range of additives to reduce CH 4 in grazing cattle and found the addition of biochar and nitrate, biochar and Asparagopsis, and citral extract to significantly reduce CH 4 emissions by 22.83%, 19.82%, and 41%, respectively. Lean and Moate [20] reviewed CH 4 reduction strategies in Australia and found that nitrate supplementation reduced emissions by 10% and feed supplemented with 3-nitro-oxypropanol (3-NOP) reduced CH 4 by 22% in beef cattle and 39% in dairy cattle. Australian research has inspired researchers in the United States to study a locally produced seaweed grown in the waters of California to reduce CH 4 in cattle.…”
Section: Feed Supplements and Additivesmentioning
confidence: 99%
See 2 more Smart Citations
“…This change has significant effects on GHG emissions intensity as the proportion of methane ascribed to maintenance is reduced. Over this time, the industry has changed from being seasonal and pasture-based (Lean 1987) to less seasonal and with greater reliance on a wide range of fodder crops, feed supplements and concentrate inputs (Rugoho et al 2017). Victorian farms evaluated for the Dairy Farm Monitor fed 61% of the metabolisable energy consumed as homegrown forages (Anonymous 2021).…”
Section: Beef Feedlot and Dairy Cattlementioning
confidence: 99%